Jason Camp on behalf of Charlotte Camp v Director General, Department of Education: [2017] WASAT 79: State Administrative Tribunal of Western Australia: Mansveld J: 29 May 2017. (11th January 2018) - Unknown
ABSTRACT: Human Rights – Freedom of religion or belief – Discrimination – Education – Claimant atheist father of atheist school student – School Creed recited at most school assemblies including phrase 'And love of God' – Students not required to attend part of assembly at which School Creed recited – Students reciting Creed permitted to omit the phrase or substitute 'God' with appropriate alternative – Claimant lodging complaint on behalf of daughter with Equal Opportunity Commission of Western Australia alleging discrimination by Director General of the Department of Education – Claimant arguing daughter subject to discrimination on ground of religious conviction in area of education – Commissioner for Equal Opportunity dismissing complaint – Whether claimant's daughter treated less favourably or suffering other detriment in relation to non-atheist comparator – Equal Opportunity Act 1984, ss 53 and 61